Plants and Their Noise Absorption: Identifying most suitable plants to reduce noise via Impedance Tube Data Analysis - Jamaludin S.M.; Hashim W.; Raj Mohamed M.A.; Mohamad Z.; Mohd Kamal N.L.; Lim A.Y.K. (Institute of Electrical and Electronics Engineers Inc., 2023)
Acoustic impedance; Acoustic noise; Acoustic wave absorption; Information analysis; Noise pollution; Plants (botany); Sound insulating materials; Data analyse and noise pollution; Exposed to; Impedance tubes; Industrial activities; Noise absorption; Plant; Plant species; Sound absorption; Urban areas; Vehicle activity; Data handling